Solvation of ionic liquids based on N-methyl-N-alkylmorpholinium cations in N, N-dimethylformamide and N, N-dimethylacetamide – Volumetric and compressibility studies. (April 2018) - Marcinkowski, Łukasz; Kloskowski, Adam; Warmińska, Dorota
Highlights: In DMF and DMA both volumes and compressibilities of ionic liquids were studied. Vϕ and KS, ϕ of DMF or DMA solutions of [Mor1, R ][TFSI] increase with increasing IL concentration. Results indicate that [Mor1, R ][TFSI] are structure breakers in DMF as well as in DMA. Obtained results show substantial impact of the cation size of the ionic liquid. Abstract: Density and sound velocity of the solutions of ionic liquids based on N -alkyl- N -methyl- morpholinium cations: N -ethyl- N -methylmorpholinium bis(trifluoromethanesulfonyl)imide, N -butyl- N -methylmorpholinium bis(trifluoromethanesulfonyl)imide, N -octyl- N -methyl -morpholinium bis(trifluoromethanesulfonyl)imide and N -decyl- N -methylmorpholinium bis(trifluoromethanesulfonyl)imide in N, N -dimethylformamide and N, N -dimethylacetamide were measured at T  = (298.15–318.15) K and at atmospheric pressure. Using experimental data, apparent molar volume and apparent molar compressibility values were calculated and fitted to the Redlich-Meyer type equation which was used to obtain partial molar volume and partial molar isentropic compressibility of the ILs at infinite dilution. By using the density data, the isobaric thermal expansibility coefficients were also estimated. The effect of alkyl chain length of the ILs, experimental temperature and properties of solvent on these thermodynamic properties were discussed.